THE INFLUENCE OF CARS ACQUISITION PARAMETERS ON THEIR IDLE HOURS ON MARSHALLING YARD - Muzykina, H. I.; Bolvanovska, T. V.; Zhorova, Ye. M. (Science and Transport Progress, 2008)
This paper is devoted to the problem of accumulating the train sets at a sorting station. An analysis of three specific processes of accumulating the train sets has been performed taking into consideration their varieties. The calculation formulas for wagon-hours of such an accumulating according to each scheme are given. The dependence between the train set accumulation parameter and the quantity of wagons in the train set that is departing from a station has been determined. It has been also determined the influence of the above mentioned parameter on the duration of lost time of wagons at a sorting station.